The effect of different storage period on some egg quality characteristics and ovalbumin levels in goose eggs - Eroglu, Mehmet; Baykalir, Yasin; Erisir, Zeki (United Arab Emirates Univ, 2021)
The aim of the current study was to investigate effect of different storage period on some external and internal egg quality and ovalbumin levels of goose eggs. The alterations of these traits have not been examined sufficiently in goose eggs during the storage. For this purpose, a total of 150 eggs were examined from 50 weeks-old German origin Embden geese. The eggs were stored under constant temperature (+4 degrees C) and similar to 60-65% relative humidity conditions for a period of 7, 14 and 21 days. The weights of 50 eggs were measured and analyzed at 7, 14, and 21 days, respectively. The weight loss, eggshell thickness, and the pH of the albumen and the yolk were different between the storage groups. Other parameters such as, shape index; weights and ratios of albumen, yolk, eggshell, and yolk color were similar between the groups. The pH values of the albumen and yolk, the weight loss, and ovalbumin levels of the albumen had increased during storage. In contrast, the eggshell thickness had declined. According to the results of this study, eggs stored under refrigeration had lower variability on quality parameters. Depending on the increase of ovalbumin with storage, it will be more appropriate to consume goose eggs by allergy-sensitive individuals freshly or after at least end of 1-week storage.
Keywords: Egg quality; Goose eggs; Ovalbumin; pH; Storage